(untitled) (International Journal of Biomedical Research, 2015)
Diabetes mellitus is a group of metabolic derangements characterised by hyperglycemia resulting from defective insulin secretion or action or both. Persistent hyperglycemia generates reactive oxygen species causing oxidative damage to cells and various biomolecules. In this study the levels of reduced glutathione antioxidant were estimated in NIDDM patients with cardiovascular disease (n=50) by HPLC method and compared to healthy controls (n=50). The results indicated that plasma glutathione levels are significantly decreased showing that antioxidant defence is lowered in diabetic patients with cardiovascular complications.